Comparison of Supratarsal Injection of Triamcinolone Acetonide and Topical Tacrolimus in the Treatment of Refractory Vernal Keratoconjunctivitis - Muneer, Madasar; Rafiq, Khurram; Asif, Muhammad (Biological and Clinical Sciences Research Journal, 2025)
Vernal keratoconjunctivitis (VKC) is a chronic allergic ocular condition commonly affecting young individuals in tropical and subtropical regions. This study aimed to compare the efficacy of supratarsal injection of triamcinolone acetonide and topical tacrolimus 0.03% in patients with refractory VKC. Methods: A randomised controlled trial was conducted at the Department of Ophthalmology, Nishtar Hospital Multan, from August 2 to February 2, 2025. Seventy patients with clinically diagnosed refractory VKC were randomised into two groups: Group A received a single supratarsal injection of triamcinolone acetonide (20 mg/mL). In contrast, Group B received 0.03% topical tacrolimus twice daily for three weeks. The primary outcome was clinical improvement of symptoms and signs (lid edema, chemosis, congestion, watering, and papillae size) assessed at three weeks. Statistical analysis was performed using SPSS v. 25. Results: Group A showed significantly higher rates of clinical improvement (85.7%) compared to Group B (60%) (p = 0.006). Resolution of lid edema (88.6% vs 68.6%, p = 0.032), chemosis (85.7% vs 62.9%, p = 0.018), and congestion (91.4% vs 65.7%, p = 0.007) was more pronounced in the triamcinolone group. Stratified analysis revealed better outcomes in male and rural patients across both groups, but triamcinolone consistently demonstrated superior efficacy. Conclusion: Supratarsal triamcinolone injection is more effective than topical tacrolimus 0.03% in managing refractory VKC in the Pakistani population. Its rapid action and ease of administration support its use as a first-line option in cases of severe or unresponsive conditions.